Proof using binomial theorem

Hi

Please take a look at the following problem:

http://i50.tinypic.com/2w5lkpd.jpg

Could someone help me out with a hint on how to prove this? I have worked out that this equation would equal 1, when x=1 and y=-2, but I could use some help on how to prove it.

Thanks in advance

Re: Proof using binomial theorem

Quote:

Originally Posted by

**zzizi**

If $\displaystyle n$ is even then

$\displaystyle 1=(1-2)^n=\sum\limits_{k = 0}^n {\left( { - 2} \right)^k }\binom{n}{k} $

Re: Proof using binomial theorem

You made it too easy (Blush)

Thank you for your help Plato!

Re: Proof using binomial theorem

Yeah, Plato has a way of doing that!